Kompetensi Pustakawan Dalam Penerapan Sistem Otomasi Perpustakaan Di Perpustakaan SMAN 21 Bandung - dadan, Dadan; Purwanda, eka (Jurnal Online Manajemen ELPEI, 2025)
The purpose of this study was to analyze the suitability of librarians' abilities in library automation services at the SMAN 21 Bandung library based on the Indonesian National Work Competency Standards (SKKNI). This study is a qualitative descriptive study. The primary data sources for this study came from interviews and observations. The researcher collected secondary data sources from documents relevant to the focus of the study. The researcher collected data using interview guidelines for librarians. The results of the study indicate that librarians at SMAN 21 Bandung have appropriate educational backgrounds and have undergone training that improves their abilities in designing, installing, and operating library automation systems. The implementation of this system has a positive impact on the effectiveness of library services and helps in fulfilling library accreditation instruments in accordance with the Decree of the Head of the National Library of the Republic of Indonesia Number 302 of 2022, which emphasizes the importance of service systems and information access. Support from the school also plays an important role in improving librarian competence through ongoing training. Thus, the SMAN 21 Bandung library is able to provide more innovative and efficient services for users.